METHODOLOGICAL APPROACHES AND PROBLEMS IN ASSESSING THE VALUE OF INTELLECTUAL CAPITAL (British Journal of Global Ecology and Sustainable Development, 2024)
The availability of knowledge resources at an enterprise determines its ability to develop sustainably and competitively. The totality of knowledge, skills and abilities (possessed by operational and management personnel), including those transformed into intangible and other assets, are considered as the intellectual capital of an enterprise. Empirically, the availability of intellectual capital at an enterprise can be identified through its success in the market and the ability to form high added value in the product. However, from a scientific and methodological point of view, approaches to assessing intellectual capital are currently not unified and do not allow obtaining an objective cost estimate of this capital.This paper presents an overview of methodological approaches to assessing the value of intellectual capital of enterprises and shows the problems of using these approaches in analytical procedures. Based on the presented materials, a conclusion was made about the need for further development of methods for assessing the intellectual capital of enterprises.